Iceshocks observed at the ice sheet surface near Mizuho Station, East Antarctica - Kenji Ishizawa (National Institute of Polar Research, 1981)
The seismological observation of iceshocks was carried out at Mizuho Station (72°42'S, 44°20'E, 2230m a. s. l.), East Antarctica, during a period from May 1978 to January 1979. From the observation it was found that the condition of iceshock occurrence was expressed by a function of both the air temperature and the changing rate of the temperature. The iceshock occurrence was explained by the fracture of the surface snow which was assumed to be a Maxwell substance. The focus positions of 45 iceshocks of a swarm were calculated by using the observed velocity of surface wave. This calculation was checked by the result of an artificial hitting on the snow surface and was found to be efficient for the determination of the focus position. The result of the calculation indicated that the focus positions were concentrated at the glazed surface where snow accumulation did not take place for a long time (for example, 2 or 3 years) and the fracture cracks were observed. Therefore, it is concluded that the iceshocks are defined as a vibration caused by the fracture crack formation at the glazed surface due to a rapid decrease in the air temperature.